Changing Scotland evidence from the British Household Panel Survey - Ermisch, John 1947-; Wright, Robert 1958- (Policy Press, University of Bristol, 2005)
Changing Scotland uses longitudinal data from the British Household Panel Survey (BHPS) to improve our knowledge and understanding of the impact of devolution on the lives of people in Scotland. It is the first time that BHPS data has been used in this way